Empowering EFL Learners Engagement through Project-Based Learning Activities - Maulina Maulina (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study investigates how English as a Foreign Language (EFL) learners' engagement and language skills are affected by project-based learning (PBL). In three cycles, twenty-eight seventh-graders participated in the research, which used a classroom action research (CAR) design in partnership with an English teacher. Student surveys, observation checklists, performance evaluations, and qualitative comments from the teacher and the students were used to gather data. According to the findings, PBL significantly increases student involvement; by the end of the cycle, 85% of students had shown consistent participation. Notably, motivation also rose, with 90% of students indicating a greater desire to learn English. There were gains in language proficiency; speaking and writing scores increased from 60% and 55% to 85% and 80%, respectively. Qualitative data showed that students felt more confident and enjoyed their learning, and they valued the PBL activities' applicability to the real world. The study also revealed problems, like lower-proficiency students' issues and initial resistance to group work, resolved with focused scaffolding and assistance. The results demonstrate that PBL can be a proper pedagogical strategy for raising student motivation and language acquisition. They also support the usefulness of PBL in fostering a more dynamic and successful EFL learning environment. Future studies could examine PBL's long-term effects and use in various educational settings.